Nomophobia syndrome and its impact on morale and behavior change in early childhood - Kamil, Nurhusna; Narjis, Kalilah; Wahyuni, Sri (Universitas Islam Negeri Ar-Raniry, 2024)
Nomophobia has become a prevalent issue which affects individuals today. This leads many to feel constantly connected to their devices. The term, derived from